2018
DOI: 10.1111/jir.12552
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in grey matter volume and its correlation with clinical symptoms in Chinese boys with low functioning autism spectrum disorder

Abstract: Background Previous studies have reported changes within grey matter (GM) volume in children with autism spectrum disorder (ASD); however, little is known about GM volume changes and the relation with symptom severity in Chinese boys with low functioning autism spectrum disorder (LFASD). Method GM volume was analysed using SPM 8 and compared between 16 boys with LFASD as well as 16 typically developing (TD) boys (using REST 1.8). Additionally, the correlation between GM volume and clinical symptoms was analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In light of the meta-analysis based on large samples, the volume of GM in the insula and inferior parietal lobe decreased (Cauda et al, 2011). Li et al (2019) have found that the GM volume of the bilateral gyrus rectus decreased, and the left rectus was negatively correlated with the clinical symptom score. Although it is not reported that the volume changes in the olfactory cortex of patients with ASD, the olfactory cortex is located at the anterior bottom of the limbic system and reciprocally connected with other structures, such as the amygdala, hippocampus, hypothalamus, the olfactory cortex is related to emotion and memory.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the meta-analysis based on large samples, the volume of GM in the insula and inferior parietal lobe decreased (Cauda et al, 2011). Li et al (2019) have found that the GM volume of the bilateral gyrus rectus decreased, and the left rectus was negatively correlated with the clinical symptom score. Although it is not reported that the volume changes in the olfactory cortex of patients with ASD, the olfactory cortex is located at the anterior bottom of the limbic system and reciprocally connected with other structures, such as the amygdala, hippocampus, hypothalamus, the olfactory cortex is related to emotion and memory.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed both increases and decreases in cerebellar GMV in adolescents with ASD with VBM analysis, which is consistent with some previous studies. 16 , 20 , 21 However, some previous studies failed to find any significant difference in cerebellar GMV between patients with ASD and TD controls, 28 , 61 even only increased 39 , 62 or decreased 41 , 63 , 64 cerebellar GMV in individuals with ASD. There may be several reasons for this discrepancy, such as the small sample size, differences in sample characteristics (eg, different developmental ages, gender, and IQ), differences in scanner techniques, including field strengths and sequence parameters, and differences in GMV analysis (postmortem autopsy vs region of interest analysis vs voxel-based approach) in these previous studies.…”
Section: Discussionmentioning
confidence: 85%
“…However, some other studies failed to report any difference in GMV values between patients with ASD and TD controls, 17 , 26–28 or even most of the brain regions with decreased GMV in Chinese boys with low functioning ASD. 41 The discrepancy of the studies above could be partly due to the relatively small sample size, different sample characteristics, limited brain regions investigated, and differences in GMV analysis (voxel-based approach vs ROI-based approach) in these previous studies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation